The effect of binders on mechanical and physical properties of Eurycoma longifolia jack extract under dry compression. - Abdul Hamid, Aziana Azlin (2010)
This thesis presents the effect of binders on mechanical and physical properties of Eurycoma longifolia jack extract’s via direct compression. In the Malay’s native tongue Eurycoma longifolia jack is commonly known as ‘tongkat ali’. Traditionally, this herb is used for treating fever, mouth ulcers, hypertension, diabetes and intestinal worms. However, its most popular local use is as an aphrodisiac for men. The main objectives of this study is to investigate the effects of different compression pressures and percentage on binders’ composition on binary mixtures of Eurycoma longifolia jack extract with binders; κ-Carrageenan and microcrystalline cellulose (MCC). In addition, validations of the compression behaviour through three classical equations were carried out. This was then used to predict the behavior of mixtures in Eurycoma longifolia jack formulation. The powders were compressed to various mixture percentages (w/w) ranging between 10 and 70 % and compression pressures ranged between 7.5 and 74 MPa at a constant compression speed of 5 mm min-1. The tensile strength values of the tablets were determined by a diametral compression test. Generally, it is predicted that Eurycoma longifolia jack extract and MCC binary mixtures has a better compressibility property in contrast to Eurycoma longifolia jack extract and к-Carrageenan binary mixtures. Furthermore, the tablets produced from Eurycoma longifolia jack extract and MCC binary mixtures had good mechanical properties, with tensile strength increasing via compression pressure while the friability values decreased. However, the tablets had poor dissolution properties; it is conclude that while tablet mechanical and physical properties can be produced from the binary mixtures, disintegrants would need to be included in the formulations to ensure sufficient active ingredient release. Additionally, from analysis of variance (ANOVA) results, the effect of the tensile strength was significantly dependent (P<0.001 in each case) on both compression pressure and binder percentage. Similarly, there was also a significant interaction (P<0.001 in each case) between pressure and binder percentage. Subsequently, the best binary mixture for Eurycoma longifolia jack extract is preferably a 30 % of MCC at 0.5 g feed powder quantity. Based on this approach, this study may provide an extensive understanding of Eurycoma longifolia jack extract compressibility and may further be used in the development of formulating herbal products.